Antibody-mediated inhibition of TNFR1 attenuates disease in a mouse model of multiple sclerosis. - Sarah K Williams; Olaf Maier; Roman Fischer; Richard Fairless; Sonja Hochmeister; Aleksandar Stojic; Lara Pick; Doreen Haar; Sylvia Musiol; Maria K Storch; Klaus Pfizenmaier; Ricarda Diem (PLoS ONE, 2014)
Tumour necrosis factor (TNF) is a proinflammatory cytokine that is known to regulate inflammation in a number of autoimmune diseases, including multiple sclerosis (MS). Although targeting of TNF in models of MS has been successful, the pathological role of TNF in MS remains unclear due to clinical trials where the non-selective inhibition of TNF resulted in exacerbated disease. Subsequent experiments have indicated that this may have resulted from the divergent effects of the two TNF receptors, TNFR1 and TNFR2. Here we show that the selective targeting of TNFR1 with an antagonistic antibody ameliorates symptoms of the most common animal model of MS, experimental autoimmune encephalomyelitis (EAE), when given following both a prophylactic and therapeutic treatment regime. Our results demonstrate that antagonistic TNFR1-specific antibodies may represent a therapeutic approach for the treatment of MS in the future.